PERDAGANGAN MYSTERY BOX DI MARKETPLACE MENURUT UNDANG-UNDANG PERLINDUNGAN KONSUMEN - Fernando, Yool (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: In this mystery box trade, consumers have rights that are protected in the UUPK Law, especially the right to information, this right is not fulfilled by business actors, causing losses because consumers get goods that are not in accordance with the promises made by business actors. The research formulates several problems, namely whether it is permissible to trade mystery boxes in the marketplace according to the UUPK and how the liability of business actors for violated consumer rights in the mystery box sale and purchase transaction in the marketplace. This research uses normative legal research methods. This mystery box trade is not allowed under UUPK because it is prohibited in Article 9 Paragraph (1) letter k and violates consumer rights in Article 4 letter b and Article 4 letter c jo Article 7 letter b of UUPK. Consumers who suffer losses can hold accountable business actors who sell mystery boxes in the form of money or goods of similar or equal value as stipulated in Article 19 Paragraph (2) of the UUPK, and business actors are obliged to fulfill demands for compensation from consumers because the UUPK adheres to the principle of always being responsible with reverse proof, so that business actors who trade mystery boxes are obliged to fulfill consumer compensation claims for losses suffered by consumers until they can prove that they are guilty or not.Keywords : Trading, Mystery Box, Consumer Protection